SOME APPROACHES OF TEACHING GRAMMAR - Farrukh Ilyosov (Research Parks Publishing LLC, 2021)
Grammar instruction is one of the most difficult issues of language teaching. Context grammar holds an important place for effective learning. It will be more motivating for learners if grammar is taught in context as students will have an opportunity to perceive how the new grammar structures work. Grammar rules are made easier if they are given in a context and teaching grammar in context provides accuracy in the target language. This article explains why we should teach grammar in context and presents tens in sample lessons. In my paper I would like to outline some topics concerning this matter, beginning with the important question if grammar teaching is actually necessary. After describing some approaches and methods in more detail and presenting briefly other important aspects in this regard, I will demonstrate my own model of grammar teaching.